Effects of supplementation of inorganic trace elements with organic trace elements chelated with hydroxy methionine on laying performance, egg quality, blood micronutrients, antioxidant capacity and immune function of laying ducks - Zhang, Yawei; Liu, Yang; Li, Chuang; Huang, Xuan; Zhang, Xu; Deng, Ping; Chen, Juan; Wu, Shujun; Wang, Huiyun; Jiang, Guitao; Dai, Qiuzhong (Frontiers in Animal Science, 2022)
This study aimed to investigate the effects of organic trace elements chelated with hydroxy methionine (OTE-HM) in diets, which substituted inorganic trace elements, on laying performance, egg quality, blood microelement content, antioxidant capacity and immune function of laying ducks. A total of 300 healthy laying ducks at age of 30 wk were randomly divided into 5 treatments and 10 ducks per replicate. The treatments included a control group (CON) which was served with basal diet supplemented with 20 mg/kg Cu, 50 mg/kg Fe, 70 mg/kg Mn, and 70 mg/kg Zn in inorganic form, and 4 OTE-HM treated groups (OTE-HM25, OTE-HM50, OTE-HM75, OTE-HM100) which were served with basal diets supplemented with OTE-HM providing trace elements (combination of Cu, Fe, Mn, Zn) at 25%, 50%, 75% and 100% of the commercial levels, respectively. Results showed that substitution of inorganic trace elements with OTE-HM did not affect egg production, qualified egg rate, average egg weight, average daily egg mass, average daily feed intake, or feed per kg egg of laying ducks (P > 0.05). Dietary with OTE-HM did not influence eggshell strength, eggshell thickness, egg shape index, eggshell ratio, yolk ratio, albumen ratio, albumen height, and Haugh unit of the sampled eggs of ducks (P > 0.05), but increased the yolk color, compared with dietary with inorganic trace elements (P < 0.01). The blood content of Cu of the laying ducks was significantly increased by OTE-HM compared with that in CON (P < 0.001), but the other elements in laying duck blood were not different among treatments (P > 0.05). OTE-HM (75% and 100%) significantly increased serum activities of glutathione peroxidase and Cu-Zn superoxide dismutase, and decreased serum content of malonaldehyde of laying ducks compared with those in CON (P < 0.05). OTE-HM (50%, 75%, and 100%) increased the serum contents of immunoglobulin G and immunoglobulin A of laying ducks compared with those in CON (P < 0.05). Collectively, replacing inorganic trace elements with 50% and 75% OTE-HM in diets did not influence the laying performance or egg quality, but improved trace element efficacy, antioxidant capacity and immune function of the laying ducks.